RESCUING THE BUSINESS RESCUE PROCESS: A CRITICAL REFLECTION ON THE AUTHORITY TO APPOINT A SUBSTITUTE BUSINESS RESCUE PRACTITIONER THROUGH THE LENS OF Shiva Uranium Limited v Mahomed Mahier Tayob 2022 (3) SA 432 (CC) - Mpofu, Kudzai; Shelton T Mota Makore (Obiter, 2024)
A determination on the authority to appoint a substitute business rescue practitioner is particularly important for its bearing on the perpetuity of business rescue proceedings. In turn, business rescue proceedings provide a rehabilitative avenue for ensuring that financially distressed companies are extricated from their financial quagmire, thereby achieving company profitability, preservation of employment, economic development and other significant social goals. Through the lenses of Shiva, the case note critically reflects on the contestation regarding who can appoint a substitute business rescue practitioner in terms of the applicable provisions of South Africa’s Companies Act 71 of 2008, wherein the court-appointed business rescue practitioner has either resigned, incapacitated or died. The case note argues that whilst the Constitutional Court in Shiva rightly held that the company or the affected person who lodged the business rescue application has the right to make the alternative appointment, depending on whether the business rescue is voluntary or compulsory, there is a need to go beyond this decision by rethinking who can be appointed as a business practitioner and well as the delegative authority of the courts. Using the classical India approach and international best practices, this case note advances the need to amend the Companies Act provisions governing the appointment of a business rescue practitioner to achieve better perpetuity and obviate the disruptions of companies’ rehabilitative process.